Domestic Explanations for War and Peace in Ukraine - Julia Strasheim (German Institute of Global and Area Studies (GIGA), 2016)
Why did Ukraine's 2004 Orange Revolution initiate a peaceful democratic transition, while the 2014 protests were followed by violent conflict? This paper complements previous studies on Russia's role in Ukraine by focusing on domestic explanations of the recent violence. It shows that structural factors were already conducive to violence in 2004, making it fruitful to analyse the role of agency to explain the 2014 conflict. It then demonstrates that while the 2004 transition introduced power-sharing guarantees that mitigated commitment problems for the relevant parties, the 2014 transition saw no such guarantees, making violence a rational strategy for the pro-Russian separatists.
Keywords: 300; Ukraine; transition; power-sharing; commitment problems; armed conflict